Generation of a simulation model for chilled PCM ceilings in TRNSYS and validation with real scale building data. (March 2019) - Yasin, Modar; Scheidemantel, Eva; Klinker, Felix; Weinläder, Helmut; Weismann, Stephan
Abstract: The evaluation and optimization of innovative building systems with simulation programs requires validated models. This paper describes a new room model for an innovative chilled ceiling with PCM (phase change materials) for the simulation program TRNSYS. The room model was validated using laboratory measurements and monitoring data of a real scale building. The chilled PCM ceiling model uses the TRNSYS type 399, which originally was made for simulating massive thermo-active building elements with PCM. This article shows, that type 399 also can be used for the chilled PCM ceiling, if certain constraints in the model geometry are taken into account. The validated model shows a good agreement with the real scale building data. A root mean square error (RMSE) for the deviation of simulated and measured temperatures of ± 0.3 °C and ± 0.6 °C could be achieved for the operative and PCM temperature, respectively. The simulated cooling power of the PCM ceiling showed a higher deviation, the RMSE was ± 0.19 kW. In a next step, the validated room model will be used to optimize the control of the chilled PCM ceiling system in a real scale building. Highlights: A chilled PCM ceiling model was implemented into existed type (399) in TRNSYS. Type 399 simulate massive thermo-active building elements with PCM. Inputs of type 399 could be determined successfully experimentally in laboratory. The model was validated using real scale building data. The validated model reached a very high accuracy with simulated temperatures.